IMPLEMENTASI ALGORITMA AES UNTUK MENINGKATKAN KEAMANAN DATA KARYAWAN PADA PT PNM CABANG KARAWANG BARAT MENGGUNAKAN PHP - Rohman, Ajar; Ramdhani , Yunita Ayu (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Security of data or information is very important for internet network users today. The case of wiretapping messages or information is one of the things that is very detrimental, with the possibility of this happening, it is necessary to increase the security of information exchange to be important. At this time, the security of this information exchange needs special attention, so this research will create a cryptographic implementation of the AES-128 algorithm for encryption and decryption of data in the form of document files). The Advanced Encryption Standards (AES) algorithm was chosen because it has a fairly good.